Soil-Metal Adhesion Due To the Variation of Soil Compactness and The Soil Moisture Content - Gatot Pramuhadi; Eduard Namaken Sembiring (PERTETA, 2001)
Soil, as the nature body, is very important in supporting the live perpetuity of the living creatures. In farm machinery and equipment application for soil tilling, soil also affects the goal of the soil tillage activities. When the soil tillage equipment and machinery are to be applied in the field. there will Qe interaction among the traction device, the blade, and the soil. The soil, which is used as a machine supporter, must have a certain consistency.Consistency is the degree of cohesion and adhesion among soil partides and soil mass resistance to the variation of shape by pressure and strength, that affected the soil deformation.